2023
DOI: 10.3390/su15032306
|View full text |Cite
|
Sign up to set email alerts
|

Financing Romanian Agricultural Cooperatives’ Investments for the 2023–2027 Horizon

Abstract: Agriculture represents an important sector of the Romanian economy, with certain vulnerabilities under the current geo-political context and pedoclimatic changes with a direct impact upon food security at national and European levels. This paper analyzes the possibilities for revitalizing the Romanian agricultural sector, which was affected by the excessive inflation (especially via the price increases of fertilizers and fuels) and drought, both generating significant cereal and agricultural production losses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Governmental support investment in research and development are considered pivotal in climate change adaptation policies and mitigating efforts. Another recent research by Zlati et al [56] showed that inconsistencies in national policies and strategies in the field of natural disasters and climate changes' risk management are the main sources of vulnerabilities for Romanian agriculture, amplified by factors such as the low technology level, low resources for research and agricultural development, and limited access to diversified financial products.…”
Section: Discussionmentioning
confidence: 99%
“…Governmental support investment in research and development are considered pivotal in climate change adaptation policies and mitigating efforts. Another recent research by Zlati et al [56] showed that inconsistencies in national policies and strategies in the field of natural disasters and climate changes' risk management are the main sources of vulnerabilities for Romanian agriculture, amplified by factors such as the low technology level, low resources for research and agricultural development, and limited access to diversified financial products.…”
Section: Discussionmentioning
confidence: 99%
“…In Western Europe and North America, Contractual Agriculture finance mechanisms were launched almost a century ago and now cover 40 to 90% of the production of some products. And of course, the banking system has taken care of the financial aspects of Contractual Agriculture for the benefit of all parties involved (indicated in [5][6][7][8][9]).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These factors have resulted in the loss of jobs in agriculture, significant increases in fuel prices, and an increase in fertilisers for agricultural crops. Taking into account climate change, there are several meteorological causes affecting the agricultural sector (e.g., significant increase in temperatures, floods, and pedological droughts) and very tense geopolitical situations, meaning that ensuring the supply of food and water to the population [1][2][3][4][5] represents a national and international priority for countries worldwide. In the case of agricultural crops that represent a large share of Romania's cultivated area, such as wheat, corn, and sunflower, their spatial distribution in the most favourable areas creates conditions for obtaining important yields proportional to the share of these crops without needing to increase cultivated areas.…”
Section: Introductionmentioning
confidence: 99%